The architectural integration of passive systems through thermal flywheel effect with evaporative cooling in Shish Mahal, Lahore Fort, Pakistan - Jahn Kassim, Puteri Shireen; mohd fauzi, Musttafa Kamal Bashar; Abdalla Abakr, Yousif; Abdul Latip, Nurul Syala (Zes Rokman Resources, 2016)
There has been much research on the comfort conditions of modern building that used natural ventilation and water bodies as medium of cooling, however much less is known about the impacts of these medium when involved to the traditional and heritage buildings especially the remnants of Mughal Empire. The study reports an ongoing research utilising computational fluid dynamics analysis to study and verify the daily and seasonal impact of passive strategies as constructed in 16th century complexes which had utilised a high degree of complexity in their passive systems through architectural means. Located in one of the forts many quadrangles, Shish Mahal pavilion are built at the north-west corner of Lahore Fort facing to the Ravi River which supplies great source of water and ideal direction to capture the prevailing winds. The architectural integration of water features are interlinked and connected to one building part to another and scattered across the pavilion in a form of certain sophisticated upper and underground water networks via water channels, pools, wells, water walls, basins and water tanks. At the basement, a provision of narrow wind tunnels as a wind scoop to funnel the north prevailing winds into the basement area are integrating with a solid central thermal mass wall associated with various waterwalls on its surface. These intellective driven passive design creating a sort of thermal flywheel effect and effective evaporative cooling strategies. The result highlight that there are significant differences in the temperature drop between the entering and leaving airflow inlets in which the long air that stay inside the basement are proved to induce higher temperature drop as much as 50% and thus suitable to maintain a fluctuation indoor temperature during the summer seasons. By studying the flow and integration of water elements through the complex, the external patterns of wind and pressure distribution around the complex and the transient impact of significant thermal mass and integrated water walls, an estimation of the internal comfort conditions within the complex during spring and summer can be estimated. It is found that the architectural elements had a significant impact and were constructed based on transient effect and such strategies had a significant impact towards comfort conditions under its climate.